The Risks and Benefits of Yoga During Pregnancy - A Literature Review - Słuchocka, Joanna; Lewalski, Tymon; Florczyk, Martyna; Płuciennik, Lidia; Lewalski, Oskar; Jeruć, Klaudia (Quality in Sport, 2026)
Background. Yoga has become an increasingly popular form of physical activity among pregnant women worldwide. As a mind-body exercise that combines physical postures, breathing techniques, and relaxation practices, yoga may influence both physiological and psychological aspects of pregnancy. Although moderate physical activity during pregnancy is widely recommended, the specific safety profile and benefits of yoga remain under continuous investigation. Aim. The aim of this literature review is to analyze current scientific evidence regarding the risks and benefits of yoga during pregnancy. Material and methods. A narrative review of clinical trials, meta-analyses, and mechanistic studies published in recent years was conducted. The analysis focused on metabolic health, musculoskeletal outcomes, cardiovascular adaptations, injury risks, respiratory and thermoregulatory responses, psychological effects, and obstetric outcomes. Results. Current research suggests that yoga practiced during pregnancy may reduce maternal stress and anxiety, improve sleep quality, alleviate low back and pelvic pain and improve glucose regulation [26–28]. Some studies indicate potential benefits in reducing the risk of gestational diabetes and improving birth outcomes, including reduced rates of preterm birth and cesarean delivery [11,12,28]. However, risks may occur especially when certain postures are performed incorrectly or without modification [8,21]. Pregnancy-related ligament laxity, balance changes, and supine positioning in late pregnancy may increase the risk of musculoskeletal strain or reduced venous return [8]. Conclusions. Prenatal yoga appears to be a generally safe and beneficial form of exercise when appropriately adapted for pregnancy. However, more large-scale randomized controlled trials are needed to determine optimal intensity, frequency, and posture modifications for pregnant practitioners.